Amino Acid Analysis Protocols - Cooper, Catherine.; Cooper, Catherine. (Methods in Molecular Biology,, 2000)
Amino acid analysis is widely used in biotechnology, biomedical, and food analysis laboratories. Amino Acid Analysis Protocols constitutes a major collection of these indispensable analytical techniques, both classic and cutting-edge, of high utility for answering specific biological questions. Common methods include those based on HPLC or gas chromatography separation and analysis after precolumn derivatization. New techniques based on capillary electrophoresis separation, high-performance anion exchange chromatography, and mass spectrometry are also presented. Since results depend heavily on the quality of the sample, most contributors have devoted a section to sample preparation, particularly to the collection and storage of bodily fluids. A new method for desalting samples prior to hydrolysis is also provided. Each method is described in step-by-step detail to ensure successful experimental results, and contains helpful notes on pitfalls to avoid, and variations that enable the methods to be used with different systems. Up-to-date and highly practical, Amino Acid Analysis Protocols offers analytical and clinical chemists, as well as a broad range of biological and biomedical investigators, a rich compendium of laboratory tools for the productive analysis of both common and uncommon amino acids.